Sustainability issues related to feeding salmonids: a C anadian perspective - Pallab Kumer Sarker; Dominique P. Bureau; Katheline Hua; Murray D. Drew; Ian Forster; Keith Were; Brad Hicks; Grant W. Vandenberg (Reviews in Aquaculture, 2013)
The issue of sustainability of salmonid culture has been the focus of considerable media coverage and debate between environmental activists and aquaculture industry stakeholders, particularly regarding the use of ingredients derived from wild fisheries (fishmeal and fish oil) in salmonid feeds. This study attempts to summarize recent data and to calculate the conversion efficiency of feed resources by C anadian farmed salmon in order objectively to assess the sustainability of this industry in this regard. Using updated information regarding domestic aquafeeds this review reports advances that have been made in diet formulation, fish in–fish out ( FIFO ) and feed conversion ratios ( FCR ) and demonstrates that production efficiency of farmed salmonids has significantly improved over time due to continued innovations in the aquafeed sector. The results suggest that the C anadian salmon aquaculture industry efficiently converts wild fish resources into high‐value fish products.